International secondary science Workbook 2 - Leng, Ho Peck; Hulme, Philippa Gardom; Jones, Catherine (Karachi: Marshall Cavendish, 2009)
Comprehensive match to Pakistan National Curriculum 2022 framework. Rigorous challenge materials that build a strong foundation for future learning. Extensive preparation for the exams to build confidence and support performance. Lots of crossover materials for seamless transition to higher levels.
Keywords: Science